A= (√3 +√2)² - (√3 - √2)²
Answers
Answered by
1
GIVEN,
OR,
SO, 4√6 IS YOUR ANSWER
Answered by
1
A=
![( \sqrt{3} + \sqrt{2})^{2} - ( \sqrt{3} - \sqrt{2})^{2} ( \sqrt{3} + \sqrt{2})^{2} - ( \sqrt{3} - \sqrt{2})^{2}](https://tex.z-dn.net/?f=%28+%5Csqrt%7B3%7D+%2B+%5Csqrt%7B2%7D%29%5E%7B2%7D+-+%28+%5Csqrt%7B3%7D+-+%5Csqrt%7B2%7D%29%5E%7B2%7D+)
=(√3)^2+(√2)^2+2×√3×√2-[(√3)^2+(√2)^2-2×√3×√2
=3+2+2√6-[3+2-2√6]
=5+2√6-[5-2√6]
=5+2√6-5+2√6
=4√6
So, your answer is 4√6
Remember ::::::::
(X+Y)^2=X^2+Y^2+2XY
(X-Y)^2=X^2+Y^2-2XY
=(√3)^2+(√2)^2+2×√3×√2-[(√3)^2+(√2)^2-2×√3×√2
=3+2+2√6-[3+2-2√6]
=5+2√6-[5-2√6]
=5+2√6-5+2√6
=4√6
So, your answer is 4√6
Remember ::::::::
(X+Y)^2=X^2+Y^2+2XY
(X-Y)^2=X^2+Y^2-2XY
Similar questions
Social Sciences,
7 months ago
Computer Science,
7 months ago
Math,
1 year ago
English,
1 year ago
Political Science,
1 year ago
Business Studies,
1 year ago